2015
DOI: 10.1371/journal.ppat.1004957
|View full text |Cite
|
Sign up to set email alerts
|

The Herpes Simplex Virus Protein pUL31 Escorts Nucleocapsids to Sites of Nuclear Egress, a Process Coordinated by Its N-Terminal Domain

Abstract: Progeny capsids of herpesviruses leave the nucleus by budding through the nuclear envelope. Two viral proteins, the membrane protein pUL34 and the nucleo-phosphoprotein pUL31 form the nuclear egress complex that is required for capsid egress out of the nucleus. All pUL31 orthologs are composed of a diverse N-terminal domain with 1 to 3 basic patches and a conserved C-terminal domain. To decipher the functions of the N-terminal domain, we have generated several Herpes simplex virus mutants and show here that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(116 citation statements)
references
References 72 publications
(188 reference statements)
7
108
1
Order By: Relevance
“…Previous analyses of biochemical properties pointed to a tightly interlocked high-affinity heterodimer formed between pUL50 and pUL53, similar to the respective homologs of other herpesviruses (9,19,30,31). A mutational analysis of the protein segments that participate in the pUL50-pUL53 interaction supported this notion, namely that a unique type of interlock is provided by N-terminal ␣-helical segments of pUL53 that become tightly hooked into a platform provided by pUL50.…”
Section: Resultsmentioning
confidence: 92%
“…Previous analyses of biochemical properties pointed to a tightly interlocked high-affinity heterodimer formed between pUL50 and pUL53, similar to the respective homologs of other herpesviruses (9,19,30,31). A mutational analysis of the protein segments that participate in the pUL50-pUL53 interaction supported this notion, namely that a unique type of interlock is provided by N-terminal ␣-helical segments of pUL53 that become tightly hooked into a platform provided by pUL50.…”
Section: Resultsmentioning
confidence: 92%
“…HSV-1 UL31 protein is a multi-functional nucleoprotein, which is transported into the nucleus via Ran-, transportin-1-and importin α1-mediated pathway [19], and this nuclear accumulation is important for viral infection [55]. Meanwhile, HSV-1 UL31 and its homologue EBV BFLF2 are both crucial for efficient viral DNA packaging and primary egress across the nuclear membrane [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports (40,47) have suggested that nuclear egress is a two-part process: First, UL31, the soluble partner of the nuclear egress complex (PRV, Uniprot Q7TBN7), binds capsids in the nucleoplasm. Afterward, UL31 acts an adapter that mediates binding to UL34, the membrane-bound partner of the nuclear egress complex (PRV, Uniprot G3G8X8).…”
Section: Discussionmentioning
confidence: 99%